Cytotoxic sesquiterpene lactones from Artemisia myriantha. (June 2020) - Zan, Ke; Chen, Xiao-Qing; Zhao, Ming-Bo; Jiang, Yong; Tu, Peng-Fei
Graphical abstract: Highlights: Two new sesquiterpene lactones were isolated from Artemisia myriantha . Biosynthesis pathway of both compounds from costunolide was discussed. 1 and 2 exhibited cytotoxic activities against human cancer cell lines HCT-8. Abstract: Chemical exploration of Artemisia myriantha Wall. ex Bess (Asteraceae) aerial parts afforded one new seco-guaianolide (1 ) and one new germacranolide (2 ). Structure elucidation of the new compounds was unambiguously performed based on HRESIMS, 1D and 2D NMR spectroscopic analyses. The two new compounds exhibited in vitro strong cytotoxic activities against human cancer cell lines HCT-8 with IC50 values of 0.76 and 0.28 μ M, respectively.